Novedades corológicas para la provincia de Córdoba (Andalucía, España). New records for the province of Cordoba (Andalusia, Spain) - López Tirado, Javier; Muñoz Álvarez, Jesús M.; Hidalgo Fernández, Pablo J. (Acta Botanica Malacitana, 2012)
New records for the province of Cordoba (Andalusia, Spain) Palabras clave. Corología, Córdoba, Andalucía. Keywords.Chorology, Cordoba, Andalusia.